Enhancing vaccine effectiveness in the elderly to counter antibiotic resistance: The potential of adjuvants via pattern recognition receptors - Myunghwan Jung; Hongmin Kim; Eunsol Choi; Min-Kyoung Shin; Sung Jae Shin (Human Vaccines & Immunotherapeutics)
Vaccines are an effective way to prevent the emergence and spread of antibiotic resistance by preventing diseases and establishing herd immunity. However, the reduced effectiveness of vaccines in the elderly due to immunosenescence is one of the significant contributors to the increasing antibiotic resistance. To counteract this decline and enhance vaccine effectiveness in the elderly, adjuvants play a pivotal role. Adjuvants are designed to augment the effectiveness of vaccines by activating the innate immune system, particularly through pattern recognition receptors on antigen-presenting cells. To improve vaccine effectiveness in the elderly using adjuvants, it is imperative to select the appropriate adjuvants based on an understanding of immunosenescence and the mechanisms of adjuvant functions. This review demonstrates the phenomenon of immunosenescence and explores various types of adjuvants, including their mechanisms and their potential in improving vaccine effectiveness for the elderly, thereby contributing to developing more effective vaccines for this vulnerable demographic.